(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. It is difficult to imagine ophthalmology today without modern methods of optical coherence tomography, which allows to diagnose pathology of all layers of the retina accurately by a scanning laser. Purpose. To determine the role of optical coherence tomography in uveitis. Material and methods. 58patients (84 eyes) aged 18 to 44 with anterior uveitis and chorioretinites participated in the study. Results. We discovered thinning of the neuroepithelium in the macular area in chronic iridocyclitis in the remission stage. There was established a significant increase (2.7 times) the height of the neuroepithelium in disseminated chorioretinites in activation of the inflammatory process, and reduced height of the neuroepithelium in the stage of scarring. Perhaps this is due to metabolic disorders in the long course of the chronic inflammation. Conclusions. We were first to discover thinning of the neuroepithelium in the macular area in chronic iridocyclitis in the remission stage. Optical coherence tomography allows us to estimate the state of all layers of the retinal uveitis.